Effect of Three-Dimensional Printed Personalized Moisture Chamber Spectacles on the Periocular Humidity - Chan Hee Moon; Jae Yong Kim; Myoung Joon Kim; Hungwon Tchah; Byeong Gak Lim; Jin Kwon Chung (Journal of Ophthalmology)
Purpose. To assess the effect of three-dimensional (3D) printed personalized moisture chamber spectacles (PMCS) on the periocular humidity. Methods. Facial computed tomography (CT) scanning was conducted on 10 normal subjects. PMCS was designed based on volume rendered CT images and produced using a 3D printer. Periocular humidity of PMCS and commercially available uniformed moisture chamber spectacles (UMCS) were measured for 30 minutes via microhydrometer. Results. The mean ambient humidity was 15.76±1.18%. The mean periocular humidity was 52.14±3.00% in PMCS and 37.67±8.97% in UMCS. The difference was significant (P<0.001). Additionally, PMCS always demonstrated lower humidity than dew points. Conclusion. PMCS made by 3D printer provides appropriate fitness for the semiclosed humid chamber. PMCS showed higher performance than UMCS. The wearing of PMCS would be an effective method to provide high enough periocular humidity in low humidity environment.